1999
DOI: 10.1177/156482659902000408
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Compliance with Weekly Iron Supplementation of Adolescent Girls by An Accompanying Communication Programme in Secondary Schools in Dar-Es-Salaam, Tanzania

Abstract: Insufficient compliance has been identified as a major contributing factor to the low effectiveness of iron-supplementation programmes. An Mention of the names of firms and commercial products does not imply endorsement by the United Nations University. 90% and 94%, respectively, in school 1, 89% and 75% in school 2, and 48% and 50% in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 19 publications
(19 reference statements)
0
48
0
1
Order By: Relevance
“…We found no systematic review on the supplementation of IFA in adolescents, but we identified two reviews on pregnant women . In our search for primary trials on adolescents, we identified 23 moderate‐quality studies from Bangladesh, Kenya, India, Indonesia, Iran, Mali, Malaysia, Mozambique, Nepal, Sri Lanka, and Tanzania . Iron dosages across those studies ranged from 60 to 120 mg/day, and folic acid ranged from 3.5 to 500 mg/day.…”
Section: Resultsmentioning
confidence: 99%
“…We found no systematic review on the supplementation of IFA in adolescents, but we identified two reviews on pregnant women . In our search for primary trials on adolescents, we identified 23 moderate‐quality studies from Bangladesh, Kenya, India, Indonesia, Iran, Mali, Malaysia, Mozambique, Nepal, Sri Lanka, and Tanzania . Iron dosages across those studies ranged from 60 to 120 mg/day, and folic acid ranged from 3.5 to 500 mg/day.…”
Section: Resultsmentioning
confidence: 99%
“…All these studies reported maternal outcomes. There were nine RCTs [60][61][62][63][64][66][67][68][69][73][74][75] and one quasi-experimental natural experiment [65]. The primary outcome reported was anemia.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Of the ten included trials, eight took place in Asia: two in Bangladesh [61,63], two in India [60,68], three in Indonesia [62,65,69], and one in Nepal [67]. Two trials took place in Africa: one in Mali [64] and one in Tanzania [66]. Seven trials were conducted in schools [60,62,64,[66][67][68][69].…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…1992 However, the ideal strategy to prevent iron deficiency would be to achieve desirable changes in food habits through education, since this would improve the nutritional status of the adolescents themselves as well as that of their families and ensure that they enter pregnancy with a satisfactory nutritional status. Also, compliance with iron supplements is likely to be greater if they are given after an appropriate health education session (Schultink et al 1993;Muro et al 1999).…”
Section: Iron Supplementation In Adolescencementioning
confidence: 99%